Lower limb orthoses: A review (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: orthoses; lower limb; disabilitydoi: 10.3329/jcmcta.v19i1.3850Journal of Chittagong Medical College Teachers' Association 2008: 19(1):33-36